2020
DOI: 10.1371/journal.pcbi.1008457
|View full text |Cite
|
Sign up to set email alerts
|

Searching through functional space reveals distributed visual, auditory, and semantic coding in the human brain

Abstract: The extent to which brain functions are localized or distributed is a foundational question in neuroscience. In the human brain, common fMRI methods such as cluster correction, atlas parcellation, and anatomical searchlight are biased by design toward finding localized representations. Here we introduce the functional searchlight approach as an alternative to anatomical searchlight analysis, the most commonly used exploratory multivariate fMRI technique. Functional searchlight removes any anatomical bias by gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Therefore, regions in neocortical grey matter commonly thought to be orthogonal to the task in univariate analyses in fact contain robust task-related information. These findings complement recent work using statistical learning to optimize voxel weights for predictive performance [8][9][10][11][12] and demonstrate that the presence of information is far more distributed across the brain than previously thought. Moreover, our analyses establish for the first time how accessible this information truly is: our models simply use mass-univariate t-statistics without any regularization or consideration of the t-statistics' joint distribution.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, regions in neocortical grey matter commonly thought to be orthogonal to the task in univariate analyses in fact contain robust task-related information. These findings complement recent work using statistical learning to optimize voxel weights for predictive performance [8][9][10][11][12] and demonstrate that the presence of information is far more distributed across the brain than previously thought. Moreover, our analyses establish for the first time how accessible this information truly is: our models simply use mass-univariate t-statistics without any regularization or consideration of the t-statistics' joint distribution.…”
supporting
confidence: 83%
“…Human fMRI work demonstrates that 100 repetitions of the same task (three participants, 9-10 sessions over three months) can uncover neocortex-wide information 19 . Decoding studies, which rely on statistical learning approaches, evidence the existence of taskspecific information outside of GLM areas [9][10][11][12][13] ; it has also been demonstrated that some of these local information patterns can be uncovered via multivariate decoding methods [20][21][22] . Similarly, recent human and macaque monkey fMRI studies demonstrate the presence of retinotopic tuning in cortical and, in macaques, subcortical regions remote from the visual cortex 23,24 .…”
Section: Figure 4 Task-relevant Information Is Pervasively Present Th...mentioning
confidence: 99%
“…By focusing on speech representations, the present study provides four empirical contributions to the investigation of auditory representations in brains and deep learning models (Yamins & DiCarlo, 2016;Keshishian et al, 2020;Huang et al, 2019;Liu et al, 2021;Kell et al, 2018;Kumar et al, 2020;Koumura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…speech-to-text using Dutch, English or Bengali). Previous studies have already shown that deep convolutional neural networks trained to classify words, musical genres (Kell et al, 2018;Kumar et al, 2020) or natural sounds (Koumura et al, 2019), generate brain-like representations, in the sense that one can find a linear correspondence between the activation of the neural networks and the activations of the brain (Figure 1). This similarity can be quantified with a "brain score" (Jung et al, 2019), a correlation between the brain measurements and a linear projection of the model's activations, under the assumption that representations are defined as linearly exploitable information (Hung et al, 2005;Kamitani & Tong, 2005;Kriegeskorte & Kievit, 2013;King et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…We previously validated that this fitting procedure produces accurate simulations of real data [ 23 ]. We have used fmrisim to evaluate the power of different experimental design parameters [ 23 ] and also to evaluate the efficacy of new analysis methods [ 86 , 87 ].…”
Section: Methods In Brainiakmentioning
confidence: 99%